Review and future trend of energy harvesting methods for portable medical devices - Paulo, J. (2010)
Portability improvement of technological devices have not been followed by energy availability of its batteries. Considering the low power consumption features of a variety of portable devices, the concept of energy harvesting from environmental sources and human body has gained a new relevance. In the search of methods and materials that suit this need, are the energy generated from the piezoelectricity, thermoelectricity and electromagnetism, among others.This paper reviews the advantages, disadvantages and future trend of energy harvesting methods, as well as its mechanisms in portable medical devices with low power consumption. The medical field is a promising sector for the use of these technologies by the need to extend the energy availability for several parameter monitoring as too allow various forms of continuous therapy. Therefore, coupling a energy harvesting system to existing battery in these devices may significantly improve their energy sustainability that at present, is one of its biggest limitations.